The venture capital lifecycle: the role of foreign venture capital in a developing startup scene in China - Hendrik J. Jansen (Asia Pacific Journal of Innovation and Entrepreneurship)
Purpose – This study aims to examine the venture capital (VC) industry, which is critical for supporting startups and typically dominated by individuals with startup experience. Recognizing the challenges faced by catching-up economies, this research seeks to understand the successful development of the VC industry in China, thereby addressing the classic “chicken or the egg” problem. Design/methodology/approach – Using a comprehensive data set from the TechCrunch database, this paper conducts both descriptive and empirical analyses. Based on theoretically grounded observations, seven hypotheses are formulated and tested using multiple linear regression. Findings – The findings indicate that foreign VC has played a significant role in establishing the VC industry in China. These foreign investors tend to lead the market and co-invest with local partners, facilitating knowledge transfer. In addition, the investment preferences of foreign VCs differ markedly from those of their local counterparts. Research limitations/implications – This study offers valuable insights for policymakers and enhances strategy development for VC firms. It also highlights potential areas for future research, further exploring the intricacies of VC in emerging markets. Originality/value – While considerable literature exists on the rise of startup funding in the USA and Europe, studies focusing on emerging economies are scarce. By using a comprehensive, yet underused data set, this research illuminates fundamental dynamics within the VC industry in these regions.